Pro12Ala polymorphism in PPAR-γ gene of impaired glucose tolerance subjects in Bangladeshi population - Faruque, Md Omar; Saha, Ayan; Khan, Imran; Hassan, Zahid; Ali, Liaquat (Journal of Bangladesh Academy of Sciences, 2021)
Pro12Ala polymorphism in PPAR-gamma (PPAR-γ) gene is associated obesity and hyperglycemia in some races, but controversy exists for other races. In this study, 113 impaired glucose tolerance (IGT) and 113 healthy control subjects were recruited. Wild type (CC), heterozygous (CG), and homozygous (GG) variants of Pro16Ala polymorphism of PPAR-γ (rs1801282) were analyzed using Chi-square test, and the polymorphism was found significantly (p=0.05, Χ2=5.875) associated with IGT subjects. Allele frequency also shows significant association with IGT subjects in the Chi-square test (p=0.026, Χ2=2.248). When the waist-hip ratio was reanalyzed according to genotype variation, the waist-hip ratio was found significantly higher among subjects with heterozygous and homozygous variants of pro16Ala polymorphism. Therefore, our study concluded that PPAR-γ P12A variants might be associated with impaired glucose tolerance. It is also documented that higher waist to hip ratio in IGT subjects may associate with heterozygous (CG) and homozygous (GG) variants of Pro12Ala mutation in the PPAR-γ gene. Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 179-189, 2020